PENGARUH FIXED ASSETS TURNOVER, DEBT TO TOTAL ASSETS RATIO DAN CURRENT RATIO TERHADAP RETURN ON ASSETS PADA PERUSAHAAN SUB SEKTOR CRUDE PETROLUM DAN NATURAL PRODUCTION (MINYAK MENTAH DAN GAS BUMI) YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2017 - Vincent Vincent (Universitas Islam Islam Sumatera Utara, 2018)
The study is to investigate the effect of fixed asset turnover, debt to total assets ratio and current ratio to return on assets both partially and simultaneously. This type of research is quantitative explanatory descriptive. Pusposive sampling technique was used to generate sample from the population and it was involved 10 companies of Sub Sector Crude Petrolum and Natural Prod which were listed on the Indonesia Stock Exchange on Period 2012-2017. The method of data collection was taken from relevant time series of Indonesia Stock Exchange documentation and it was analyzed by using multiple linear regression, test coefficient of determination, partial test and simultaneous test. The results of the study showed that either partially or simultaneously fixed asset turnover, debt to total assets ratio and current ratio did not affect return on assets. The study is to investigate the effect of fixed asset turnover, debt to total assets ratio and current ratio to return on assets both partially and simultaneously. This type of research is quantitative explanatory descriptive. Pusposive sampling technique was used to generate sample from the population and it was involved 10 companies of Sub Sector Crude Petrolum and Natural Prod which were listed on the Indonesia Stock Exchange on Period 2012-2017. The method of data collection was taken from relevant time series of Indonesia Stock Exchange documentation and it was analyzed by using multiple linear regression, test coefficient of determination, partial test and simultaneous test. The results of the study showed that either partially or simultaneously fixed asset turnover, debt to total assets ratio and current ratio did not affect return on assets.